(untitled) (Al-Academy, 2024)
This research is concerned with studying the operations of idealistic philosophy in the structure of the Iraqi theatrical performance. It is divided into four chapters, including the first chapter (the methodological framework of the research), which is topped by the research problem based on the following question: What are the operations of idealistic philosophy in the structure of the Iraqi theatrical performance? While the importance of the research focused on the current study is that it examines the study of (idealism), and special propositions and ideas related to and intertwined with theatre and monitoring their uses in the Iraqi theatrical performance. The need for it is that it benefits researchers and students in institutes and colleges of fine arts and those working in the field of theatrical art. As for the goal of the research, it aims to identify the works of idealistic philosophy in the structure of the Iraqi theatrical performance. The chapter concluded by defining the most important terms mentioned in the title of the research. The second chapter, entitled Theoretical Framework, included two sections entitled in the following order: The first topic: Idealism according to the philosophical perspective. The second topic: The works of idealism in the structure of the international theatrical presentation. Then the chapter concluded with the indicators that resulted from the theoretical framework and previous studies. As for the third chapter, it included the research procedures, which is the research community that includes one research sample, which is a model for the research, and the research sample that was limited to the play (Blood Horse), directed by Jabbar Jodi in 2007 AD. The researcher concluded at the end of this research, the results that emerged from the analysis of the research sample were mentioned, including: According to the results, the researcher built some conclusions, then presented a set of recommendations accompanied by some proposals that she found complementary to the research. This was in the fourth chapter of this research, and the researcher did not neglect to mention the list of sources that she relied on in this study